A monster is coming! - Harrison, David L. (David Lee), 1937-; Wilhelm, Hans, 1945- (New York : Random House, 2011)
When Inchworm overhears Mama Bug tell Baby Bug that she eats like a monster, he cries out in fear and sets off a chain reaction of animals trying to hide from the horrible beast they believe is coming.
1.6
K-3
K-3
Keywords: Fear -- Juvenile fiction; Food habits -- Juvenile fiction; Forest animals -- Juvenile fiction; Fear -- Fiction; Food habits -- Fiction; Forest animals -- Fiction; Eating customs -- Fiction; Fear -- Fiction; Forest animals -- Fiction; Readers (Elementary).